The mediating role of self-esteem in the relationship between parenting style and academic dishonesty among undergraduates in Malaysia - Khoo, Zhi Yin; Soo, Melanie Yu Teng; Ong, Li Ying (2021)
Parenting style is a common topic to study the children’s behaviour. It was indicated that parenting plays an important role in shaping the development of children, such as their self-esteem level. Besides, it was believed that the act of academic dishonesty was associated with the perceived parenting styles and self-esteem of children. Hence, the present study aims to study the mediation effect of self-esteem between parenting styles and academic dishonesty. A qualitative, cross-sectional, and correlational study was adapted for this research. Primary data was collected through online survey method and a convenience sampling method was used to recruit participants. 283 undergraduates aged between 18 to 24 years old were recruited for the study. Surprisingly, the result demonstrated that there is no significant relationship between parenting styles and academic dishonesty. Besides, results also showed that the relationship between parenting styles and self-esteem was not significant. Mediation effect of self-esteem on parenting styles and academic dishonesty was not found as well. In terms of gender, researchers found that there is a difference in academic dishonesty but not in self-esteem. In a nutshell, the result of this paper was inconsistent with the past studies. Future research can continue to seek understanding on the inconsistency.